ETHNOMEDICINAL SURVEY OF NOAGAON DISTRICT, BANGLADESH - Yesmin, F.; Shahidullah, Md.; Nasir Uddin, S. M.; Rahmatullah, M. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Noagaon district falls within the greater Rajshahi Division in the north-western part of Bangladesh. We conducted an ethnomedicinal survey amongst the Kavirajes (traditional medicinal practitioners) of the district to gather information on medicinal plants to treat various ailments. Information on 21 plants distributed into 17 families was collected. The various medicinal plant species (with family name in parenthesis) included Barleria sp. (Acanthaceae), Crinum sp. (Amaryllidaceae), Annona squamosa (Annonaceae), Holarrhena antidysenterica (Apocynaceae), Bombax ceiba (Bombacaceae), Canna indica (Cannaceae), Wedelia chinensis (Compositae), Ipomoea mauritiana (Convolvulaceae), Cycas sp. (Cycadaceae), Ephedra sp. (Ephedraceae), Adenanthera pavonina (Leguminosae), Cajanus cajan (Leguminosae), Mucuna pruriens (Leguminosae), Urena lobata (Malvaceae), Cocculus hirsutus (Menispermaceae), Stephania japonica (Menispermaceae), Piper longum (Piperaceae), Glycosmis pentaphylla (Rutaceae), Murraya koenigii (Rutaceae), Tectona grandis (Verbenaceae), and Curcuma zedoaria (Zingiberaceae). The various ailments treated by whole plant or plant parts were food poisoning, flatulency, dysentery, indigestion, infertility, pain, paralysis, snake bite, debility, bronchitis, jaundice, anemia, skin infections, spermatorrhea, abscess, skin infections, reduced breast milk in lactating mothers, fever, diabetes, and helminthiasis.